Impact of water-accomodated fractions (WAF) of Bombay High crude oil on the regulation of nitrogen metabolism in the tropical teleost Oreochromis mossambicus (Peters) - Mathews, Jehosheba P.; Philip, Babu (Indian Journal of Fisheries, 2011)
Oreochromis mossambicus (Peters) was exposed to 1.5 ppm, 3.0 ppm and 5.0 ppm concentrations ofwater-accommodated fractions (WAF) of Bombay High crude oil for 21 days and different parameters likeprotein, protease, free amino acids, ammonia, urea, glutamate dehydrogenase, alanine amino transaminase andaspartate amino transaminase were estimated in liver, gill, heart, muscle and blood . A significant dose-dependentvariation was observed in liver, gill, heart and muscle tissues.